Model Komunikasi Antarbudaya Etnik Madura dan Etnik Melayu - Aminullah Aminullah; Puji Lestari; Sigit Tripambudi (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2015)
This study aims to determine the model of intercultural communication and intercultural communication barriers between Madurese and Malays in Roban, Singkawang West Kalimantan. It is research a qualitative research. Data were collected through observation, document review, and interviews. The result shows that the form of communication is mutual respect between cultures and ethnic customs that appreciates each other. Malay ethnic honors and respects customs of Madurese ethnic and vice versa. Inhibiting factors of intercultural communication are less Madurese can mingle with Malay community, lack of knowledge of Madurese ethnic tradition or custom of the Malay ethnic community, lack of desire to follow customs and traditions of local community as well as low frequency of interaction with community.